2016
DOI: 10.1126/sciadv.1600708
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical placode in reptile scale morphogenesis indicates shared ancestry among skin appendages in amniotes

Abstract: Researchers show that scales, feathers, and hairs of reptiles, birds, and mammals evolved from the scales of their common reptilian ancestor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
130
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 55 publications
11
130
1
1
Order By: Relevance
“…However, recent evidence has suggested that integumentary epithelial appendages are historically homologous, at least throughout all amniotes on the basis of the anatomical placode with conserved expression and function of GRN members [4]. Our results suggest this historical homology extends even further into vertebrate phylogeny and may encompass the integumentary epithelial appendages of all extant jawed vertebrates.…”
Section: Discussionmentioning
confidence: 50%
“…However, recent evidence has suggested that integumentary epithelial appendages are historically homologous, at least throughout all amniotes on the basis of the anatomical placode with conserved expression and function of GRN members [4]. Our results suggest this historical homology extends even further into vertebrate phylogeny and may encompass the integumentary epithelial appendages of all extant jawed vertebrates.…”
Section: Discussionmentioning
confidence: 50%
“…Recently, we have shown that scaffoldin of the chicken is expressed in the embryonic periderm and in epithelial cells that support the morphogenesis of claws and feathers by providing a transient epithelial scaffold which degenerates after maturation of these skin appendages31. These data contributed to the evolutionary-developmental model that connects the embryonic archosaur scale and feathers16171853. The identification of the genes encoding scaffoldins 1 and 2 will facilitate the determination of their expression during embryonic development and during the shedding cycle of snakes in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Signaling between the epidermis and the underlying dermis controls the patterning of the epidermis and the formation of skin appendages15161718. While differentiation of keratinocytes in the mammalian epidermis involves continuous alterations of cell structures and movement of cells towards the body surface, keratinocyte differentiation in squamates results in the formation of distinct non-interconvertible layers that remain stable for several weeks before they are shed together89.…”
mentioning
confidence: 99%
“…In zebrafish and in bearded lizard, mutations in the EDA/EDAR pathway lead to the absence of scales and teeth (Fig. b, c) . In chick scaleless mutant, the absence of ESC and F is due to a FGF20 deletion (Fig.…”
Section: Conservation Of Placode Regulating Pathwaysmentioning
confidence: 97%